Common and specific gene regulatory programs in zebrafish caudal fin regeneration at single-cell resolution - Chen, Yujie; Hou, Yiran; Zeng, Qinglin; Wang, Irene; Shang, Meiru; Shin, Kwangdeok; Hemauer, Christopher; Xing, Xiaoyun; Kang, Junsu; Zhao, Guoyan; Wang, Ting (Genome Research, 2025)
Following amputation, zebrafish regenerate their injured caudal fin through lineage-restricted reprogramming. Although previous studies have charted various genetic and epigenetic dimensions of this process, the intricate gene regulatory programs shared by, or unique to, different regenerating cell types remain underinvestigated. Here, we mapped the regulatory landscape of fin regeneration by applying paired snRNA-seq and snATAC-seq on uninjured and regenerating fins. This map delineates the regulatory dynamics of predominant cell populations at multiple stages of regeneration. We observe a marked increase in the accessibility of chromatin regions associated with regenerative and developmental processes at 1 dpa, followed by a gradual closure across major cell types at later stages. This pattern is distinct from that of transcriptomic dynamics, which is characterized by several waves of gene upregulation and downregulation. We identified and in vivo validated cell-type-specific and position-specific regeneration-responsive enhancers and constructed regulatory networks by cell type and stage. Our single-cell resolution transcriptomic and chromatin accessibility map across regenerative stages provides new insights into regeneration regulatory mechanisms and serves as a valuable resource for the community.
10.1101/gr.279372.124